Dose-sparing effects of novel adjuvants and aluminum hydroxide on two different vaccines in a neonatal mouse model - Molina Estupiñan, Jenny Lorena; Foroutan Pajoohian, Poorya; Pedersen, Gabriel Kristian; Christensen, Dennis; Marchi, Serena; Montomoli, Emanuele; Bjarnarson, Stefanía P.; Jonsdottir, Ingileif; Aradottir Pind, Audur Anna (Frontiers in Immunology, 2025)
Childhood vaccination provides protection against infectious diseases, but multiple vaccinations are required to achieve this. In situations like influenza epidemics or COVID-19 pandemic, vaccine demands may exceed production capacity, highlighting the need for dose-sparing strategies. Adjuvants can boost and modulate immune responses to vaccines and could reduce the antigen doses needed to confer protection. Herein we evaluated the dose-sparing effects of the novel adjuvants dmLT, mmCT, CAF01, and CAF08b and alum (aluminum hydroxide) on primary neonatal antibody (Ab) response to a conjugate vaccine against Streptococcus pneumoniae, Pn1-CRM197, and a recombinant influenza hemagglutinin (HA) protein vaccine. The primary Ab levels of neonatal mice immunized once with a full dose of Pn1-CRM197 or HA were low. mmCT and CAF08b enhanced Pn1-specific IgG Abs elicited by fractional doses of Pn1-CRM197, providing eightfold dose sparing of the vaccine, whereas dmLT and CAF01 provided fivefold and twofold dose sparing, respectively. These adjuvants elicited protective Pn1-specific Ab levels against bacteremia (91%–63%) and pneumonia (50%–38%) in neonatal mice when combined with a half-dose of Pn1-CRM197. In addition, mmCT, CAF01, and CAF08b enhanced the persistence of Pn1-specific IgG Ab-secreting cells (ASCs) in bone marrow compared with a full dose of vaccine only. With the influenza HA vaccine, CAF08b provided 40-fold dose sparing, while CAF01 and mmCT provided twofold dose sparing. CAF08b induced the micro-neutralization (MN) titers above protective levels in 100% and 86% of mice receiving 1/8 and 1/40 of HA dose, respectively, and CAF01 in 88% and 50% of mice receiving 1/4 and 1/8 dose of HA, respectively, whereas only 38% of mice receiving a full-dose HA without adjuvant reached the protective MN levels. Furthermore, these adjuvants provided cross-protective Abs and ASCs against a closely related heterologous influenza strain. In contrast, aluminum hydroxide did not provide any dose-sparing effects. Collectively, our results demonstrate that mmCT, CAF01, and CAF08b enhanced the protective humoral responses and had large dose-sparing effects on both Pn1-CRM197 and HA vaccines, although the adjuvant effect was clearly vaccine-dependent. The results support the potential use of safe adjuvants in situations when vaccine production capacity is limited, including vaccination of pediatric populations that may be of high risk.